Phase-cycling schemes for pump–probe beam geometry two-dimensional electronic spectroscopy - Zhang, Zhengyang (2013)
Experimental demonstrations and detailed theoretical explanations are provided for a thorough understanding of the various phase-cycling schemes in an optical pulse shaper assisted two-dimensional electronic spectroscopy (2DES) in a pump–probe beam geometry. We show that two and three-step phase-cycling schemes can be employed to retrieve both rephasing and nonrephasing 2D spectra. The studies were performed on the Qy transition of chlorophyll a.